Practicing Multicultural Education through Religiously Affiliated Schools and Its Implications for Social Change - Rohman, Miftahur; Lessy, Zulkipli (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
Having varied ethnicities, cultures, religions, or faiths, Indonesia is considered a multicultural nation in today’s world. This equity can be dangerous; but also can be advantageous if myriad interests of citizens are able to be nurtured through education, including religious schools. The research was conducted to explore multicultural practices in the State-owned Islamic High School (MAN) 3 and the Catholic High School (SMA) Stella Duce 2 in Yogyakarta Indonesia. Data was gathered via a qualitative method by means of comparative study, aiming at seeking similarities and differences in promoting multicultural education values. Findings show similarities of teachers’ attitudes and characteristics as a facilitator, accommodator, or assimilator whereas the differences include their leadership role in intrareligious dialog at MAN 3 and dialog leaders at SMA Stella Duce 2. Other issues include diverse understandings of religion and its perceived violence. The research formulates two categories of teachers as being multicultural-intrareligious pluralists and multicultural-intrareligious humanists. It also discusses implications on social change as a result of the cultural interchange at those schools.